Judicial Lawfare: Analysis of Legal Arguments against Abortion Rights in Peruvian Courts - Camila Gianella; Brenda Álvarez (Revista Direito GV)
Abstract This article analyzes the puzzling case of Peru, a country highlighted as an example of the internationalization of sexual and reproductive health and rights norms through supranational litigation, but where these legal victories have not prompted an expansion of abortion rights. Through the analysis of three judicial cases, with a focus on the legal arguments and strategies, the article argues that two features of the abortion legal mobilization in Peru are key to understand the lack of more positive developments: 1) formalistic feature of Peruvian Courts, that offers little space toward recognizing additional grounds for abortion, as has been the case in other Latin American countries; 2) innovative capacity of anti-abortion legal mobilization, that have forced to create a tacit alliance between the movement toward the recognition of abortion rights and the State, to defend the (restricted) abortion rights in the country.